Musculoskeletal Disorders and Dental Practice - POLICY STATEMENT, FDI; PTS, STANOWISKO (Journal of Stomatology, 2015)
Due to high prevalence and their impact on life, health and productivity musculoskeletal disorders (MSDs) present important hazards for dentists. This FDI statement is intended to draw the attention of dentists to the multifactorial etiology of these disorders and emphasize the importance of prevention.